Pola Interaksi Antar-lembaga dan Reformasi Tata Kelola Keamanan Maritim Indonesia: Bakamla RI - Adi Wibawa; Muhammad Ridha Iswardhana; Hidayat Chusnul Chotimah (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2021)
Maritime security is an essential aspect for an archipelagic country like Indonesia. In addition, as stated by President Joko Widodo, maritime defense forces are also one of the five pillars in realizing Indonesia as the "World Maritime Axis." However, unfortunately, there are still many problems that we can identify in the management of Indonesian maritime security and defense. One of the most fundamental problems is many authorized ministries/agencies, causing overlapping authorities in our territorial waters. This study aims to determine the pattern of interaction between ministries/agencies and how the government should carry out the government towards the ministry/institution in question. The researcher uses qualitative methods, and the data used are secondary data obtained from books, journal articles, and other sources that can be accessed online. In analyzing the interaction pattern between ministries/agencies, the researcher uses the theory of inter-agency working. As a result, the interaction between the competent ministries/agencies has not shown good synergy in maintaining maritime security in Indonesian waters. Furthermore, the era of technological disruption has demanded bureaucratic reform 4.0 by emphasizing three (3) things, including innovation, collaboration, and maximizing the use of information and communication technology. The researcher concludes that there is a need to reform Indonesia's maritime security governance by strengthening the synergy between ministries/agencies or even simplifying the number of authorized ministries/agencies based on the single agency multi-task system. In addition, it is necessary to use quality technology to support effectiveness and efficiency in protecting the security of marine waters in Indonesia.